(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
This paper uncover many stories of those homes where women’s were beaten very badly specially in past three decades. How human rights in india tries to stop or minimize these domestic violences.